CRITICAL REVIEW OF SOPHISTIC MODELS OF PERSUASION REGARDING THEIR SIGNIFICANCE AND INFLUENCE ON MODERN POLITICAL RHETORIC - Vasilić, Veronika; Stošić, Sanja (Srpska politička misao, 2026)
Sophists were professional teachers of primarily rhetoric who imparted their knowledge to young men in the Greek world. They were active in the fifth century BC, and their influence, above all on rhetoric, was enormous both on later centuries and classical Greek authors, and up to the present day. This is especially reflected in political rhetoric, which is based on persuasion, i.e., convincing listeners by using various rhetorical techniques, the foundations of which were laid by the sophists. It is a common opinion that democratic campaigns should be based on rational argumentation based on the truth, but in practice, this is not the case, and they are more often based on opinion and not necessarily on truth. The basis of doxastic argumentation was laid by the sophists. This paper will analyze certain attitudes of the sophists as well as fragments of their works that indicate that their thought is still present in the political space, using and analyzing the best examples from the most famous sophistic representatives, namely Protagoras and Gorgias. Some of their principles are implemented in modern political campaigns in democratic systems, which reproduce the structural models of persuasion developed by the sophists, where the emphasis was on performance, the impression that was left and effective presentation.
Keywords: sophists; rhetoric; persuasion; political rhetoric; Protagoras; Gorgias; sophistic argumentation